Internalizing Qur’anic–Hadith Values in the Formation of Personality and Morality in Indonesia: A Psychological Approach - Nurul Budi Murtini; Abdul Hadi; Mohammad Ridlo Masyhari; Binti Nurisnaini; Nira Arumsari; Irfan Yuhadi; Ardian Dananjaya (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study examines how Qur’anic and Hadith values function as psychological meaning systems that shape the personality and morality of Indonesian society. Using a qualitative library-based method, this research integrates Qur’anic and Hadith sources namely the values of tauhid, amanah, ihsan, mizan, tazkiyah, and syura with contemporary psychological theories emphasizing moral awareness, public integrity, prosocial personality, personality balance, and moral foundations in decision-making. The findings demonstrate that Qur’anic and Hadith values can structure the personality and morality of Indonesian society, including: (1) the internalization of tauhid as moral awareness, (2) the internalization of amanah as public integrity, (3) the internalization of ihsan in fostering a prosocial personality, (3) the internalization of mizan as personality balance, (4) the internalization of tazkiyah as self-regulation, and (5) the internalization of syura as the internalization of amanah in strengthening public integrity.